Avaliação da salubridade ambiental como fator de contribuição à gestão de resíduos sólidos urbanos. estudo de caso: Bacia Hidrográfica Baixo Pardo/Grande (SP) - Alvares, Maria Eugênia Gonçalez (2020)
Environmental health is related to the health and environmental conditions of a given region, municipality or watershed. The Environmental Health Indicator (ISA) is a planning tool that assists in less immediate and more realistic decision-making and allows comparison of health among different municipalities. The main objective was to evaluate the environmental health of the municipalities belonging to Water Resources Management Unit 12 (UGRHI 12) - Baixo Pardo/Grande River Basin (SP) as a contributing factor for urban solid waste management (USWM). A methodology consisted of a bibliographic review, calculation of the Environment Health Indicator (ISA) using the method of the State Sanitation Council (CONESAN, 2019), adaptations of the method and list of results for USWM. Data collection was performed exclusively on a digital platform. The data were inserted in the ISA equation, but due to the absence of some data, sub-indicators were adapted. It was possible to calculate the ISA for the twelve municipalities and UGHRI 12. The results indicated that of the twelve municipalities evaluated, Altair, Colômbia, Jaborandi e Orlândia were classified as wholesome (76%<ISA<100%) and the rest (Barretos, Bebedouro, Colina, Guaraci, Icém, Morro Agudo, Terra Roxa e Viradouro) presented average healthiness (51%<ISA<75%). In analysis of the solid waste indicator (Irs), four municipalities (Colina, Icém, Terra Roxa e Viradouro) presented a level of average healthiness and therefore, services can be improved, raising the population’s quality of life and, consequently, healthiness. As for USWM, alternatives can be implemented such as the establishment of an intermunicipal consortium for landfill, the development of reverse logistics and selective collection for recyclable solid waste of high commercial value, the structuring of cooperative services to guarantee and valorization of labor, among other actions.